Influence of microstructure on the application of Ni-Mn-In Heusler compounds for multicaloric cooling using magnetic field and uniaxial stress. (15th September 2021) - Pfeuffer, Lukas; Gràcia-Condal, Adrià; Gottschall, Tino; Koch, David; Faske, Tom; Bruder, Enrico; Lemke, Jonas; Taubel, Andreas; Ener, Semih; Scheibel, Franziska; Durst, Karsten; Skokov, Konstantin P.; et al.
Abstract: Novel multicaloric cooling utilizing the giant caloric response of Ni-Mn-based metamagnetic shape-memory alloys to different external stimuli such as magnetic field, uniaxial stress and hydrostatic pressure is a promising candidate for energy-efficient and environmentally-friendly refrigeration. However, the role of microstructure when several external fields are applied simultaneously or sequentially has been scarcely discussed in literature. Here, we synthesized ternary Ni-Mn-In alloys by suction casting and arc melting and analyzed the microstructural influence on the response to magnetic fields and uniaxial stress. By combining SEM-EBSD and stress-strain data, a significant effect of texture on the stress-induced martensitic transformation is revealed. It is shown that a <001> texture can strongly reduce the critical transformation stresses. The effect of grain size on the material failure is demonstrated and its influence on the magnetic-field-induced transformation dynamics is investigated. Temperature-stress and temperature-magnetic field phase diagrams are established and single caloric performances are characterized in terms of ΔsT and ΔTad . The cyclic ΔTad values are compared to the ones achieved in the multicaloric exploiting-hysteresis cycle. It turns out that a suction-cast microstructure and the combination of both stimuli enables outstanding caloric effects in moderate external fields which can significantly exceed the single caloric performances. In particular for Ni-Mn-In, the maximum cyclic effect in magnetic fields of 1.9 T is increased by more than 200 % to -4.1 K when a moderate sequential stress of 55 MPa is applied. Our results illustrate the crucial role of microstructure for multicaloric cooling using Ni-Mn-based metamagnetic shape-memory alloys. Graphical abstract: Image, graphical abstract